Performance evaluation of key energy-saving technologies in public institutions based on heat pump system in cold regions - Xin Liu; Xin Lai; Kailiang Huang; Hua Li; Guohui Feng; Zixiang Zhao; Shuai Hao (Energy and Built Environment)
The energy systems of public institutions experience unsatisfactory actual operation and improper operation management, and the level of building energy consumption is increasing annually. Research on the application of key energy-saving technologies in public institutions is an effective method to improve building energy efficiency and reduce energy wastage. In this study, the aperformance of key energy-saving technologies in public institutions were considered as the research object. Combined with the characteristics of different energy-saving technologies and relevant national standards, the evaluation indices were selected from four aspects: comprehensive energy efficiency, economy, environment, and operation management. According to the results of expert investigations and measured data, the index weight was determined using the artificial neural network and expert scoring methods, and a complete evaluation system of indices was built. There were 4 first-level, 10 second-level, and 11 third-level evaluation indices in the evaluation system. The evaluation indices of each level with the largest weights were the comprehensive energy efficiency of the buildings (0.532), technical energy efficiency (0.331), and water pump power consumption to heat (cold) transmission ratio (0.167). The evaluation system for key energy-saving technologies in public institutions is useful for operation managers to identify the weak points of system operations and formulate timely optimisation schemes. This evaluation system can be used as a valuable reference for improving the energy-saving levels of public institutions.